IDENTIFICATION AND CHARACTERIZATION OF NEW IMPURITIES IN DEXAMETHASONE OPHTHALMIC SUSPENSION - KUMAR, BHUPINDER; MUDHULKAR, RAJU; GUNDEKARI, SREEDHAR; RAO, DAMA VENUGOPALA; ANAMALAGUNDAM, LAKSHMIPRIYA (International Journal of Applied Pharmaceutics, 2025)
Objective: This study was intended to identify two unknown impurities (Imp-A and Imp-B) observed at trace level in the six-month stability samples of dexamethasone ophthalmic suspension subjected to accelerated conditions (40 °C/75% relative humidity) using chromatographic and spectroscopic techniques. Methods: During a six-month stability study of dexamethasone ophthalmic suspension, two unknown impurities were detected at level of exceeding the specification (0.20%) in chromatographic analysis. Impurities were isolated, enriched by preparative HPLC and characterized by using sophisticated spectroscopic techniques, including nuclear magnetic resonance (NMR), high-resolution mass spectrometry (HR-MS) and infrared (IR). Efficient and selective separation of these impurities was achieved using ultra-high performance liquid chromatography (UHPLC) on a Waters Acquity Bio H-Class System with XBridge C18 column (150 mm × 4.6 mm, particle size 3.5 µm) column at 40 °C. The mobile phase consisted of 0.02M ammonium formate and acetonitrile with detection at 240 nm using a photodiode array (PDA) detector. The results demonstrated that this mass-compatible UPLC method is suitable for the identifying and quantifying Imp-A and Imp-B in the dexamethasone ophthalmic suspension samples. Results: Two impurities were formed in dexamethasone ophthalmic suspension samples under accelerated stability conditions, which were identified by spectroscopic techniques like LC-HRMS, NMR (1D and 2D) and IR. Major structural modifications of Imp-A and Imp-B with respect to dexamethasone were found on carbon C17. Mono-isotopic mass of 379.1921 [M+H]+and empirical formula of C21H28FO5 for Imp-A, and mono-isotopic mass of 407.1838 [M+H]+and empirical formula of C22H28FO6 for Imp-B observed during LC-HRMS study found in line with theoretical mono-isotopic mass and empirical formula for both impurities. The chemical shifts and splitting patterns observed in the 1D and 2D NMR spectra indicated the presence of a steroidal ring system in both impurities, consistent with the core structure of dexamethasone, suggesting that Imp-A and Imp-B are structurally related to the parent compound. The 2D 1H-13C HSQC spectra of Imp-A and Imp-B revealed correlations between hydrogen and carbon atoms, supporting their structural relationship with dexamethasone. Additionally, 1H-13C HMBC spectra confirmed the presence of a conjugated steroidal ring system in both impurities. Based on the combined LC-HRMS and NMR data, the structures of Imp-A and Imp-B were characterized and found to be related to dexamethasone. Conclusion: The LC-HRMS method developed for the identification of unknown impurities of dexamethasone was found to be highly sensitive and selective. This method is capable of detecting trace level of impurities in dexamethasone and can used for the identifying unknown impurities of dexamethasone drug product. Combination of different spectroscopic techniques provides a pivotal tool for elucidating the structure impurities at trace level.